Single-molecule dynamics suggest that ribosomes assemble at sites of translation in Bacillus subtilis - Stoll, Joshua; Zegarra, Victor; Bange, Gert; Graumann, Peter L. (Frontiers in Microbiology, 2022)
Eukaryotic cells transcribe ribosomal RNA and largely assemble ribosomes in a structure called the nucleolus, where chromosomal regions containing rRNA operons are clustered. In bacteria, many rRNA operons cluster close to the origin regions that are positioned on the outer borders of nucleoids, close to polar areas, where translating 70S ribosomes are located. Because outer regions of the nucleoids contain the highest accumulation of RNA polymerase, it has been hypothesized that bacteria contain “nucleolus-like” structures. However, ribosome subunits freely diffuse through the entire cells, and could thus be assembled and matured throughout the non-compartmentalized cell. By tracking single molecules of two GTPases that play an essential role in ribosomal folding and processing in Bacillus subtilis, we show that this process takes place at sites of translation, i.e. predominantly at the cell poles. Induction of the stringent response led to a change in the population of GTPases assumed to be active in maturation, but did not abolish nucleoid occlusion of ribosomes or of GTPases. Our findings strongly support the idea of the conceptualization of nucleolus-like structures in bacteria, i.e. rRNA synthesis, ribosomal protein synthesis and subunit assembly occurring in close proximity at the cell poles, facilitating the efficiency of ribosome maturation even under conditions of transient nutrient deprivation.